2x2 - 4xy + 3y2 = 1, for x

Suppose you have a linear equation in x and y, 3x - 2y = 6, and you are asked to solve for "the indicated variable." Somewhere, there will be an indication as to whether you are to solve for x or for y. Let's say the indicated variable is y, so we want to solve this equation for y.

In general, we want to "undo" what has been "done" to y. We see that y has been multiplied by -2, and that 3x has been added. We reverse these steps like this:

3x - 2y = 6

(3x - 3x) - 2y = 6 - 3x (we have subtracted 3x from both sides. This leaves the y term by itself after we finish the math: 3x-3x=0, so we can drop it.)

-2y = 6 - 3x (the simpler form of the previous equation)

y = (6 - 3x)/(-2) = (6/-2) - (3x/-2) (we divide both sides by -2)

y = -3 + (3/2)x (carrying out the arithmetic, taking care to pay attention to signs)

This equation y = -3 + (3/2)x is the original equation solved for y. We could have solved for x. The steps would be similar, but not identical.

Here's your clue:

1) undo what has been done to the variable of interest

2) keep the "=" sacred: Whatever you do on one side of it must also be done on the other side of it

3) pay attention to signs.

In general, we want to "undo" what has been "done" to y. We see that y has been multiplied by -2, and that 3x has been added. We reverse these steps like this:

3x - 2y = 6

(3x - 3x) - 2y = 6 - 3x (we have subtracted 3x from both sides. This leaves the y term by itself after we finish the math: 3x-3x=0, so we can drop it.)

-2y = 6 - 3x (the simpler form of the previous equation)

y = (6 - 3x)/(-2) = (6/-2) - (3x/-2) (we divide both sides by -2)

y = -3 + (3/2)x (carrying out the arithmetic, taking care to pay attention to signs)

This equation y = -3 + (3/2)x is the original equation solved for y. We could have solved for x. The steps would be similar, but not identical.

Here's your clue:

1) undo what has been done to the variable of interest

2) keep the "=" sacred: Whatever you do on one side of it must also be done on the other side of it

3) pay attention to signs.

1/2 gt to the power of 2, for g

P=2(l+w)

solve for w

solve for w

S=pr(h+k) solve for h

V=4/3pabc solve for c

help me!!

V=4/3pabc solve for c

help me!!

P + 2L + 2 W

______

1 - s

______

1 - s